Prefabrication of a Lithium Fluoride Interfacial Layer to Enable Dendrite-Free Lithium Deposition - Jie Ni; Yike Lei; Yongkang Han; Yingchuan Zhang; Cunman Zhang; Zhen Geng; Qiangfeng Xiao (Batteries, 2023)
Lithium metal is one of the most attractive anode materials for rechargeable batteries. However, its high reactivity with electrolytes, huge volume change, and dendrite growth upon charge or discharge lead to a low CE and the cycle instability of batteries. Due to the low surface diffusion resistance, LiF is conducive to guiding Li+ deposition rapidly and is an ideal component for the surface coating of lithium metal. In the current study, a fluorinated layer was prepared on a lithium metal anode surface by means of chemical vapor deposition (CVD). In the carbonate-based electrolyte, smooth Li deposits were observed for these LiF-coated lithium anodes after cycling, providing excellent electrochemical stability for the lithium metal anode in the liquid organic electrolyte. The CE of Li|Cu batteries increases from 83% for pristine Li to 92% for LiF-coated ones. Moreover, LiF-Li|LFP exhibits a decent rate and cycling performance. After 120 cycles, the capacity retention of 99% at 1C is obtained, and the specific capacity is maintained above 149 mAh/g. Our investigation provides a simple and low-cost method to improve the performance of rechargeable Li-metal batteries.